Information Management: A Catalyst to Organizational Performance among University Employees - Kehinde Akanb, Felicia; Temitope Adetunji, Adeniyi (International Journal of Psychosocial Rehabilitation, 2019)
Organisation exists for a purpose and this purpose can only be achieved through combinations of resource especially human, capital and environment. These resources cannot function without communicating with each other properly making management of such information an important factor in organizational performance. This study is set to examine the cause of an event that triggers organisational performance through information dissemination and management. The problem of mismanagement of information between faculties and staff as well as the spread of distorted information or ‘manufactured lies’ is a thing of concern in the University setting. While other researchers have worked on the technical aspect of information management, this study focused on the managerial aspect of information dissemination. The paper adopts a survey research approach to the discussion of issues raised in order to put up a position of how information is disseminated and managed in the Nigerian university. The study established that information management is distinctively different from information technology. While investment in information technology has not yielded the corresponding impact on organisational performance, investment in information management has positively influenced organisational performance. The thrust of this paper is, therefore, to raise awareness and expand our knowledge of the need to improve information management in the institution of higher learning that can increase better performance in order to help in achieving the vision and mission of the institution.